(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2021)
This research aimed at describing Bacanâ€™s Coastal Fishing Port Profile, discovering marketing activities and fish distribution, and determining alternative structuring strategies of marketing system arrangement and fish distribution at Bacanâ€™s Coastal Fishing Port. By descriptive analysis, market and fish distribution analysis, and SWOT analysis, the results showed that Bacanâ€™s Coastal Fishing Port had 2 criteria for marketing establishment and 4 marketing channels; the marketing channels for fresh TCT fish from fishermen is done through wholesaler which is categorized as monopsony market structure and selling cooperation is binding; the highest marginal profit is not for fishermen, and the biggest percentage of Fisherman’s share is marketing channel through UPI. The strategies needed to improve or to rearrange the marketing system and fish distribution are strengthening capital marketing access for fishermen through cooperative institution; activating PPDI by auction system; revitalizing SLIN program; consolidation stock data, demand and price by involving stakeholders; restructuring marketing channel and fish distribution design from producers to consumers; consolidation and communicating with the local Fish Processing Unit; providing convenience in accessing markets and promotion marine and fishery products on domestic and overseas markets; development information system of DPI and weather in Maluku Sea; development of fishermen’s human resources for handling catches on board; and development the processing industry of fishery product.